백혈병 세포 침윤에 의한 안구 돌출 1예 - 전호민; Ho Min Jeon; 최웅철; Woong Chul Choi (Daihan angwa haghoi jabji, 1998)
백혈병은 소아기의 악성종양중 가장 빈도가 높고 안와종양의 2-11%를 차지한다. 저자들은 3세 남앙서 중추신경계를 포함한 전신적인 백혈병이 단안으 안구돌출을 일으켜 골수천자 및 생검으로 확진하여 호학요법만으로 호전된 1예를 경험하였기에 문헌고찰과 아울러 보고하는 바이다(한안지 39:1891~1896,1998). Leukemia accounts for 2 to 11 percent of orbital tumors in childhood. We experienced a case of unilateral proptosis by leukemic cell infiltration, involving the central nervous system in a 3 year old boy. Acute lymphoblastic leukemia was confirmed by bone marrow aspiration cytology and biopsy, and proptosis improved with chemotherapy alone. We report this very unusual condition with a review of pervious reports(J Korean Ophthalmol soc 39:1891~1896,1998).